The Cry of Tamar : Violence against Women and the Church's Response, Second Edition - Cooper-White, Pamela, 1955- (Book collections on Project MUSE., 2012)
In this comprehensive, practical, and gripping assessment of various forms of violence against women, Pamela Cooper-White challenges the Christian churches to examine their own responses to the cry of Tamar in our time. She describes specific forms of such violence and outlines appropriate pastoral responses. The second edition of this groundbreaking work is thoroughly updated and examines not only where the church has made progress since 1995 but also where women remain at unchanged or even greater risk of violence.